From Is to Ought: How Scientific Research in the Field of Moral Cognition Can Impact the Criminal Law - Levin S. Güver (Cognitio, 2019)
Rapid technological advances in the field of neuroscience and cognitive psychology are claiming to have solved the millennia-old puzzle of moral cognition. If true, our societal structures – and with that the criminal law – would be gravely impacted. This paper concerns itself with four distinct theories stemming from the disciplines above, taking an in-depth look at the Dual Process Theory by Joshua Greene and juxtaposing the findings to the consequentialist and retributivist theories of punishment present in the American Criminal Law Doctrine.